2022
DOI: 10.33215/sjom.v5i1.724
|View full text |Cite
|
Sign up to set email alerts
|

Does Environmental Knowledge Matter? Social Influence and Pro-Environmental Behavior in University Students: An Indirect Effect Model

Abstract: Purpose- This study aims to provide an analytical framework that focuses on environmental knowledge as a mechanism through which social influence enhances pro-environmental behavior among university students. Design/Methodology- The research employed quantitative strategy, cross-sectional survey design, and systematic random sampling techniques to obtain data from a sample of 335 university students using a structured self-administered questionnaire. The study hypotheses were tested using Hayes Process Macro v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…A large percentage of variations can be attributed to factors not included in the study. The result of this study on the significant relationship between the environmental locus of control and environmental literacy is found similar to the findings of Patel et al (2019) and Simiyu et al (2022) which revealed that internal environmental locus of control is the strongest predictor environmental attitudes and skill. This is supported by Yang & Weber (2019) which stated the finding that internal Locus of control and literacy in environment of students in Magsaysay National High School environmental locus of control had an indirect positive impact on the environment.…”
Section: Resultssupporting
confidence: 86%
“…A large percentage of variations can be attributed to factors not included in the study. The result of this study on the significant relationship between the environmental locus of control and environmental literacy is found similar to the findings of Patel et al (2019) and Simiyu et al (2022) which revealed that internal environmental locus of control is the strongest predictor environmental attitudes and skill. This is supported by Yang & Weber (2019) which stated the finding that internal Locus of control and literacy in environment of students in Magsaysay National High School environmental locus of control had an indirect positive impact on the environment.…”
Section: Resultssupporting
confidence: 86%